DYNAMICS OF CHANGE IN FUNCTIONAL STATES IN THE BODY OF CHILDREN UNDER THE INFLUENCE OF ENVIRONMENTAL CONDITIONS - Azimova Nozanin To’ymurodovna (European Science Publishing, 2023)
This article provides information on the effects of changes in environmental conditions on the children’s organism as well as the dynamics organism of changes in functional states.
Keywords: iodine, calcium, natural,resources, plant, oxygen.